Advanced soft magnetic composite materials for AC applications with reduced iron losses. (December 2015) - Frayman, L.; Quinn, S.; Quinn, R.; Green, D.; Hanejko, F.
Abstract : Achieving high density with soft magnetic composite (SMC) materials requires compaction pressures exceeding 700 MPa; resulting in significant work hardening of the iron powder particles, increasing the DC magnetic coercive force along with a corresponding increase in the hysteresis loss portion of the total core loss. Annealing the as-compacted component at temperatures at or above 650°C reduces the coercive DC force and tends to decrease the AC core losses provided that the insulation layer is stable during the annealing cycle. Detailed in this paper are preliminary results utilising a novel electrically insulating inorganic coating applied to iron particles targeting fabrication of SMCs for low to medium frequency applications. This novel coating uniformly covers the iron powder and can withstand a curing temperature ≥650°C (≥1200°F). Various curing temperatures and processing conditions were evaluated and will be discussed in terms of mechanical properties as well as magnetic performance. This new material will be compared to the existing high density SMC grade that was cured at 450°C (932°F).